Enhancing the Stability and Bioaccessibility of Tree Peony Seed Oil Using Layer-by-Layer Self-Assembling Bilayer Emulsions - Wen-Sen He; Qingzhi Wang; Zhishuo Li; Jie Li; Liying Zhao; Junjie Li; Chen Tan; Fayong Gong (MDPI AG, 2023)
Tree peony seed oil (TPSO) is an important plant source of n-3 polyunsaturated fatty acid (α-linolenic acid, ALA > 40%) that is receiving increasing attention for its excellent antioxidant and other activities. However, it has poor stability and bioavailability. In this study, a bilayer emulsion of TPSO was successfully prepared using a layer-by-layer self-assembly technique. Among the proteins and polysaccharides examined, whey protein isolate (WPI) and sodium alginate (SA) were found to be the most suitable wall materials. The prepared bilayer emulsion contained 5% TPSO, 0.45% whey protein isolate (WPI) and 0.5% sodium alginate (SA) under selected conditions and its zeta potential, droplet size, and polydispersity index were −31 mV, 1291 nm, and 27%, respectively. The loading capacity and encapsulation efficiency for TPSO were up to 84% and 90.2%, respectively. It was noteworthy that the bilayer emulsion showed significantly enhanced oxidative stability (peroxide value, thiobarbituric acid reactive substances content) compared to the monolayer emulsion, which was accompanied by a more ordered spatial structure caused by the electrostatic interaction of the WPI with the SA. This bilayer emulsion also exhibited markedly improved environmental stability (pH, metal ion), rheological properties, and physical stability during storage. Furthermore, the bilayer emulsion was more easily digested and absorbed, and had higher fatty acid release rate and ALA bioaccessibility than TPSO alone and the physical mixtures. These results suggest that bilayer emulsion containing WPI and SA is an effective TPSO encapsulation system and has significant potential for future functional food development.